Achieving glycaemic control: Current and future management opportunities - Calvert, M; Shankar, A; Mcmanus, R; Freemantle, N (2008)
Diabetes poses a serious clinical and financial challenge (Turner et al, 1999). The prevalence of diabetes is continuing to increase and estimates suggest that by the year 2036, there will be approximately 20% more cases of type 2 diabetes in the UK than in 2000, with associated rapid increases in micro- and macrovascular complications and subsequent reduced quality of life (Bagust et al, 2002; Morgan et al, 2006). It has been estimated that by 2040-2050, health care expenditure for diabetes could increase to £2.2 billion. In the UK, most people with type 2 diabetes are managed entirely within primary care and increasing numbers of practices are developing management skills previously available only in secondary care (Khunti and Ganguli, 2000). Tight glycaemic control has been shown to reduce the risk of microvascular complications for people with type 2 diabetes, including renal failure and retinopathy. It also reduces the risk of macrovascular complications and appears potentially cost effective, but in practice, is often not achieved (UKPDS, 1998; Clarke et al, 2005; Dormandy et al, 2005). In this paper, we describe current practice, guidelines and potential barriers to optimal management of type 2 diabetes in primary care. We consider different approaches for improving care, including new theraphies, gudeline development and education.